TECTONIC ISOLATION OF THE LEVANT BASIN OFFSHORE GALILEE-LEBANON - EFFECTS OF THE DEAD SEA FAULT PLATE BOUNDARY ON THE LEVANT CONTINENTAL MARGIN, EASTERN MEDITERRANEAN - Schattner U.; Ben-Avraham Z.; Lazar M.; Hüebscher C. (My University, 2006)
The continental margin of the central Levant, offshore northern Israel and southern Lebanon is characterized by a sharp continental-oceanic crustal transition, exhibited on the bathymetry as a steep continental slope. At the base of the slope a narrow zone of faulting deforms the upper Messinian-recent sedimentary sequence. Further into the basin no major deformations are observed. However, onland a restraining bend along the Dead Sea fault plate boundary results in the formation of the Lebanon and anti-Lebanon mountain ranges, which exhibit a large positive isostatic anomaly not compensated at depth. All these geologic features follow a NNE-SSW trend. A dense network of multi-channel and single-channel seismic profiles, covering 5000 km of ship-track offshore northern Israel and southern Lebanon, was analyzed for the purpose of characterizing the continental margin. Additional seismic surveys covering the area between the Levant margin and the Cyprean arc were examined. Data were then incorporated with magnetic, gravity and earthquake measurements to reveal the deep crustal structure of the area and integrated with bathymetry data to describe the behavior of the young sedimentary basin fill. Results indicate that the Levant basin, offshore northern Israel and southern Lebanon (up to Beirut) is more-or-less unaffected by the intense tectonic deformation occurring onland. The transition between the deformed area onland and the undeformed Levant basin occurs along the base of the continental slope. Along the base, the upper Messinian-recent sedimentary sequence is cut by two sets of faults: shallow growth faults resulting from salt tectonics and high angle faults, marking the surface expression of a deeper crustal discontinuity - the marine extension of the Carmel fault zone. The central Levant continental margin is being reactivated by transpressional faulting of the marine continuation of the Carmel fault, at the base of the continental slope. This fault system coincides with the sharp continental-oceanic crustal transition, and acts as an isolator between the Levant basin and its land counterpart. To the north, this feature may initiate the formation of a new triple junction, with the Latakia ridge (part of the eastern Cyprean arc) and the East Anatolian fault. © 2006.
Keywords: CARMEL FAULT ZONE; DEAD SEA FAULT; EASTERN MEDITERRANEAN; LEVANT BASIN; TECTONIC ISOLATION; Messinian; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский